Pengaruh Perceived Usefulness, Perceived Ease of Use dan Perceived of Risks Terhadap Minat Penggunaan ShopeePay di Kota Padang (Studi Kasus Pada Mahasiswa Politeknik Negeri Padang) - Hana Ariqah; Reno Fithri Meuthia; Dedy Djefris (Politeknik Negeri Padang, 2023)
This study examines factors influencing the intention to use ShopeePay in Padang using adoption theory of TRA, namely TAM and TPB. The research is to find out how the Politeknik Negeri Padang students intention to use ShopeePay, in terms of perceived usefulness, perceived ease of use, and perceived of risks variables. A total of 108 completed and usable questionnaires were collected from Politeknik Negeri Padang students to test the hypotheses. The results show that perceived usefulness and perceived ease of use have the most significant influence on intention to use ShopeePay in Padang. Meanwhile, perceived of risks not have a strong influence on intention to use ShopeePay in Padang. These findings are expected to be a reference or consideration for developing or improving the ShopeePay service system.